Utilization of Lime Derived From Mussel Freshwater Shells (Pilsbryoconcha exilis) to Increase Swamp Water pH For Catfish (Pangasius sp.) culture - Dade - Jubaedah; Marsi - -; Marini - Wijayanti (Sriwijaya Journal of Environment, 2019)
The water pH of swamp land is generally low (below 4) and becomes a constraint in catfish culture that requires pH 6.5-8.5. In this current study, the low pH value of water was overcome by liming using lime produced from the mussel freshwater shells. The purposes of this study were to determine the best dosage of lime derived from mussel freshwater shells to increase the pH of swamp water, as well as its effect on the survival rate and growth of catfish fingerlings. This study used Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments used were the different dosages of lime derived from mussel freshwater shells (P1=4,000, P2=5,000, P3=6,000, P4=7,000 kg/ha equivalent CaO) and calcite (CaCO3) as control (P5= 6,000 kg/ha equivalent CaO). The result showed that P4 was the best treatment according to data of swamp water pH increased from 3.4 to 8.23, soil pH increased from 3.4 to 8.22, survival rate (100%), absolute growth of weight (56.59 g) and length (13.37 cm) and feed effeciency (113.06%).